A comparative study of clinical characteristics and quality of life between obese and non-obese asthmatics - Rao, Shobitha; Bilagi, Rakesh; B K, Radhe; Hiregoudar, Ruchik; Narayanan, Vishnu (Asian Journal of Medical Sciences, 2024)
Background: Asthma is a chronic inflammatory disorder arising from heterogenic geneenvironment interactions. Obesity is one of the risk factors for asthma. Evidence shows that several inflammatory markers are active in obese and overweight patients. There is growing evidence that obesity can affect the course and control of asthma. Aims and Objectives: The study was done to compare clinical characteristics, spirometry variables, and quality of life among obese and non-obese asthmatics. Materials and Methods: The study was a crosssectional comparative study conducted in a tertiary care hospital using a semi-structured pre-tested questionnaire. Detailed history and examination, quality of life using AQLQ score, and spirometry severity were assessed. Results: A total of 80 patients, 40 obese asthmatics and 40 non-obese asthmatics were included in the study. The study found that most subjects belonged to the age group of 31–40 years and body mass index of 30.89±1.94 among the obese group and 23.19±3.77 in non-obese, respectively. The majority had symptoms of breathlessness and wheezing in both groups. The mean forced expiratory volume in 1 s was similar in both groups. However, the mean forced vital capacity was lower in the obese group. The asthma control test (ACT) score was poorer in obese group as compared to nonobese group (7 in obese vs. 15 in non-obese). The dosage of inhaled steroids was higher in the obese group. Conclusion: The symptomatology was similar among the two groups. Restrictive abnormalities, higher asthma symptoms with lower ACT scores, and higher dosages of medications were seen in obese asthmatics as compared to non-obese patients.